Dimensões políticas da comunicação pública: estudo sobre a divulgação de pesquisas do IBGE e do IPEA - Flôres, Janecir Cardoso (2025)
Having established public communication in Brazil as an object of study, the Research problematizes the quality of information offered to Brazilian society in order to point out evidence about communicative effectiveness in its political dimension. In the context of 21st century transformations and mediated social relations, the general objectives of the research are to reflect on political interference in government bodies, as well as on the importance of public service to social reality. The aforementioned study has IBGE and IPEA as institutions chosen for their vocation to science and for illustrating the processes that configure the carrying out of research of public interest. Based on the option for a qualitative approach methodology (bibliographical-documentary), the questionnaire and interview were used with the aim of knowing, respectively, the opinion of communication managers and directors of the institutions studied in the context of the proposed topic. The theoretical framework demonstrated throughout the Research includes the discussion formulated by scholars in the area on a series of subjects and themes, highlighted in specific sections or diluted in the text of the Thesis, as follows: a) the history of public communication in Brazil and the studies in this scientific field (Ferreira, Haswani, Novelli, etc.); b) the political dimension of public communication in relation to citizen rights and the meaning of democracy in the context of the social imaginary (Arendt, Castoriadis, Habermas, Luhmann, etc.); c) theories and concepts for understanding and defining public communication (Bucci, Duarte, Zémor, etc.); d) organizational planning and professional practices in the field of public communication (Bueno, Kunsch, Torquato, etc.); and e) the obstacles and challenges for the future of the area according to the metaphors presented (Lara; Rolando etc.). The expected result is based on providing possible contributions from public communication and the Brazilian State to society beyond the mission of informing citizens about public policies and their rights, as an instrument capable of effecting pressing social transformations